Causes, Challenges and Solutions of Terrorism in Newly Merged Districts: A Critical Appraisal - Prof Dr. Amir Ullah Khan; Inam Ul Haq; Syed Rizwan Haider Bukhari; Mr. Imran Igra (Al-Qanṭara, 2025)
There is no part of the world that is not affected by broad effects of global terrorism which is as old as the entire civilization of man. But the expansion of modern warfare and the technological field has increased the magnitude and the level of complexity of terrorism making it not only includes conventional terrorism but also nuclear terrorism, chemical terrorism, biological terrorism and cyber terrorism. The consequences of the Global War on Terrorism have greatly impacted Pakistan and more importantly the individuals of the former Federally Administered Tribal Areas (FATA) and the Khyber Pakhtunkhwa. The structure of this paper is four-fold. The first part is the introduction of the study including the research methodology. The second part examines how the respondents have an idea of such concepts like militancy and terrorism and how the traditional systems of governance including the Malik and Jirga systems and the Political Administration were helpful in service delivery and combat of terrorism before the 25 th Amendment of the Constitution of Pakistan (1973). The third part focuses on the work of the District Administration, the District Police and the Pakistan Army in terms of delivery of services and in the programs of counter-terrorism after 25th Amendment. The last section shows the root causes of militancy, major policy suggestions and conclusion of the study.